Keteladanan Guru Pak Terhadap Karakter Peserta Didik Sesuai Dengan Kehendak Allah ( Mazmur 1 : 1 – 2 )( Studi kasus Sma N 1 Pantai Cermin ) - Nurliani Siregar; Jesika Enjel Desnaria Sitorus; Sri Renata Sagala; Yanti Sintia Purba; Juis Pahotan Simbolon; Dina Lorensa Ginting; Putri Siregar; Mikhael William Gabriel Siahaan Siahaan; Ages Svalma Sibagariang; Putri Tresia Manurung (Departement of Mathematics Education, 2024)
This study aims to explore the influence of the exemplary Christian Religious Education Teacher (PAK) on the formation of the character of students at SMA Negeri 1 Pantai Cermin in accordance with the will of God as stated in Psalm 1:1-2. This verse emphasizes the importance of staying away from the ways of the wicked and meditating on God's words day and night as the basis for the formation of a godly character. The purpose of this study is to examine how PAK teachers become role models in daily life and in teaching, as well as how this affects the character of students. The research method used was through in-depth interviews with PAK teachers, classroom observations, and questionnaires distributed to students. The results of the study show that the example of PAK teachers who live in accordance with Christian values, such as honesty, love, and integrity, play a significant role in shaping students' character that reflects the will of God. Teachers who consistently live the teachings of the Bible in their daily interactions and in their teaching methods are able to inspire and motivate students to live a life in accordance with Christian teachings.